Analysis of Impact of Speed Range on Energy Consumption of Low-speed Maglev Train - JIAO Yanjun; HUANG Haokai; LIU Shaoke (机车电传动)
The relationship of the maglev train speed was analyzed with its operating characteristic and traction efficiency respectively, the concept of the average resistance of the maglev train was put forward, and the average speed and the average resistance were used to reflect its size of energy consumption and running time on the flat-straight road with fixed-length. According to the experimental data, the influence of different running speed limit of the maglev train on operation energy consumption and running time consuming was also analyzed, and three conclusions were drawn which were instructive to the energy-saving drive of the low-speed maglev train on the flat-straight road.